2006
DOI: 10.1187/cbe.06-04-0160
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Classroom Teaching Technique To Help Students Understand Michaelis-Menten Kinetics

Abstract: A new, simple classroom technique helps cell biology students understand principles of Michaelis-Menten enzyme kinetics. A student mimics the enzyme and the student's hand represents the enzyme's active site. The catalytic event is the transfer of marbles (substrate molecules) by hand from one plastic container to another. As predicted, increases in marble concentration increase the number of marbles transferred per unit time (initial rate, V 0 ) until the turnover number becomes rate limiting and V 0 approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 3 publications
2
30
0
1
Order By: Relevance
“…After teaching the class on the basic concepts concerning enzymes and enzyme kinetics, the Michaelis-Menten equation was introduced. The following points were clarified with the example of a marble experiment described by Runge et al 16 : physical meanings of K m and V max , turnover number, and obtaining K m and V max values using a reciprocal plot. In the marble experiment, 2 plastic containers (1 and 2) are used.…”
Section: Ligand-receptor Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…After teaching the class on the basic concepts concerning enzymes and enzyme kinetics, the Michaelis-Menten equation was introduced. The following points were clarified with the example of a marble experiment described by Runge et al 16 : physical meanings of K m and V max , turnover number, and obtaining K m and V max values using a reciprocal plot. In the marble experiment, 2 plastic containers (1 and 2) are used.…”
Section: Ligand-receptor Interactionsmentioning
confidence: 99%
“…One of the important concepts that was clarified by the marble experiment was why, at higher concentrations of substrate, an enzyme reaches saturation. After demonstrating the marble experiment, 16 students identified that if the number of enzymes remains constant and, the substrate concentration is high, the velocity of the reaction must asymptotically approach a maximum. Sets of enzymes with different turnover numbers and K m values were provided to students in the classroom, with opportunities for them to apply their knowledge of K m values and turnover numbers to solidify their understanding.…”
Section: Ligand-receptor Interactionsmentioning
confidence: 99%
“…Teacher teams in this study were asked to repeat the method previously published by Runge et al (19), but without use of the blindfold, to assess if the collected kinetic data were hyperbolic. Teams (after being given sufficient time to complete their data collection and analysis) were surveyed in open discussion.…”
Section: Guided Inquiry Stage I: Repeating the Runge Et Al Methodmentioning
confidence: 99%
“…However, many biochemical or cellular processes deviate significantly from such conditions. Voituriez et al have shown that the state attained by reversible diffusion-limited reactions at time t = ∞ is generally not a true thermodynamic equilibrium, but rather a nonequilibrium steady state, and that the law of mass action is invalid [151,152], see also [153][154][155][156].…”
Section: Membrane Transportmentioning
confidence: 99%